Service Quality, Tourism Facilities, and Islamic Literacy Culture As Predictors Of Revisit Intention At Baloli Tourism Village - Kasmiati; Edi Marzudi; Sultan (CV Putra Publisher, 2026)
This study aims to analyze the effect of service quality, tourism facilities, and Islamic literacy culture on tourists' revisit intention in Baloli Tourism Village, North Luwu Regency. It employs a quantitative explanatory approach using a survey method with 100 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS, including validity and reliability tests, classical assumption tests, as well as hypothesis testing through t-test, F-test, and coefficient of determination (R²). The results show that simultaneously, all three variables significantly influence revisit intention (R² = 93.3%). Partially, tourism facilities have a positive and significant effect, and Islamic literacy culture is the most dominant variable. Notably, service quality shows a significant negative effect (β = –0.162, p = 0.030), which is interpreted as a saturation effect: when tourists rate service quality as already meeting high expectations (mean = 4.70, strongly agree), it no longer serves as a primary differentiator but rather a baseline prerequisite, while Islamic literacy culture becomes the main driver of revisit intention. These findings suggest that tourism village development must integrate service, physical facilities, and Islamic values as a sustainable competitive strategy.